2008
DOI: 10.1097/dad.0b013e3181822057
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art of Teledermatopathology

Abstract: Teledermatopathology may involve real-time transmission of images from distant locations to consulting pathologists by the remote manipulation of a robotic microscope. Alternatively, the static store-and-forward option involves the single-file transmission of subjectively preselected and captured areas of microscopic images by a referring physician. The recent introduction of virtual slide systems (VSS) involves the digitization of whole slides at high resolution thus enabling the user to view any part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…These diseases undergo biopsy almost exclusively by physicians without sufficient experience in dermatological disorders (mostly young residents and general practitioners); nonetheless, these cases, too, represent a diagnostic challenge for dermatopathologists sitting at the microscope. All of these limitations, as well as the intrinsic difficulties associated with histopathologic diagnosis of cutaneous inflammatory disorders, 11,20 probably account for a score lower than expected by the 9 dermatopathologists. On the other hand, even considering the limiting factors just mentioned there was a statistically highly significant improvement in the number of correct diagnoses, number of differential diagnoses, and level of confidence, thus showing that even under these conditions, the addition of clinical pictures clearly helps in making a better histopathologic diagnosis of inflammatory skin disorders.…”
Section: Discussionmentioning
confidence: 89%
“…These diseases undergo biopsy almost exclusively by physicians without sufficient experience in dermatological disorders (mostly young residents and general practitioners); nonetheless, these cases, too, represent a diagnostic challenge for dermatopathologists sitting at the microscope. All of these limitations, as well as the intrinsic difficulties associated with histopathologic diagnosis of cutaneous inflammatory disorders, 11,20 probably account for a score lower than expected by the 9 dermatopathologists. On the other hand, even considering the limiting factors just mentioned there was a statistically highly significant improvement in the number of correct diagnoses, number of differential diagnoses, and level of confidence, thus showing that even under these conditions, the addition of clinical pictures clearly helps in making a better histopathologic diagnosis of inflammatory skin disorders.…”
Section: Discussionmentioning
confidence: 89%
“…1,2,4,6,8,9,25,26 Technical factors include field selection error, inadequate photographic sampling, and poor image quality. In our study, field selection error was identified as the major contributing factor in the initial misdiagnosis of the toxic epidermal necrolysis case (Table I, case 26), in which the diagnostic area was not present in static telepathology images submitted for review.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44][45] Teledermatopathology is achieved by (i) video-image (dynamic) analysis; (ii) store and forward (static); and (iii) web-based virtual slide system. [46] A virtual slide system is a recently Kanthraj Teledermatology practice developed technology where a robotic microscope is used; any field of the specimen is selected for better digitalization at any required magnification at the discretion of the dermatopathologist. [43] Teledermoscopy Pigmented skin lesions and melanoma are analyzed based on the dermoscopic criteria [47,48] that depend on characteristic changes in epidermis and dermis.…”
Section: Teledermatopathologymentioning
confidence: 99%